Endoscopic ultrasound in the assessment of advanced duodenal adenomatosis in familial adenomatous polyposis. Issue 1 (20th September 2019) - Labib, Peter L; Goodchild, George; Turbett, James P; Skipworth, James; Shankar, Arjun; Johnson, Gavin; Clark, Sue; Latchford, Andrew; Pereira, Stephen P
Abstract : Objective: Current surveillance strategies for duodenal adenomatosis in familial adenomatous polyposis (FAP) miss malignancies and underestimate cancer risk in ampullary disease. This study aimed to evaluate the utility of endoscopic ultrasound (EUS) in the assessment of FAP patients with duodenal and/or ampullary polyposis referred for surgical intervention. Design: A retrospective analysis of FAP patients undergoing index EUS between December 2006 and May 2015 was performed. Follow-up was completed in January 2018, including review of all EUS procedures and surgical interventions (median follow-up 6 years). Results: Fifty-five patients underwent 188 EUS procedures. Six patients (11%) developed malignancy (three duodenal, three ampullary). Ampullary cancer risk was underestimated by Spigelman stage and overestimated by Kashiwagi classification. Ultrasound findings were poor predictors of malignancy, with common bile duct dilatation being the only finding present in one EUS prior to a diagnosis of ampullary cancer. The best predictors of ampullary malignancy were an ampullary polyp size >3 cm and an increase >1 cm in ampullary polyp size. Ampullary polyp size >3 cm provided the best predictive value, correctly identifying two of the three cases of ampullary cancer and both patients with high-grade dysplasia. EUS biopsy failed to detect malignancy later confirmed by surgical histology in two patients. Conclusion: EUS surveillance confers little additional benefit to standard endoscopic surveillance in FAP patients. The best predictor of ampullary malignancy is an ampullary polyp >3 cm; this could be regarded as a relative indication for surgery.